Analysis of the Impact of Productive Zakat on Mustahik's Welfare Case Study: (Badan Amil Zakat Nasional Provinsi Lampung) - Fuad Buntoro; Marselina Marselina; Heru Wahyudi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to see the impact of productive zakat on the welfare of mustahik Baznas Lampung Province. This study uses a qualitative descriptive approach with data collection through in-depth interviews (deep interviews) and secondary data from various sources. The results of this study indicate that productive zakat has a positive impact on the welfare of mustahik. Because with this productive zakat assistance, it is mustahik to get additional work, increase income, and fulfill the daily needs and school needs of their children.